The intensification of mass transfer processes for the reactions in complex-reactive heterogeneous systems - Васильєв, Михайло Ілліч (Technology audit and production reserves, 2015)
Based on the study of the theory of heat and mass transfer processes, known models of interfacial heat and mass transfer in the article concretized hydrodynamic side of transport processes. It allows reasonable approach to the methods of phase transfer intensification: mechanical, pulsating, thermal of formation and collapse of bubble, medium movement on the curved channels. It is shown that each method can be implemented in a corresponding design of the device. The basic constructions as devices and their contact devices are considered in detail, the advantages and disadvantages are shown. It is found that the development and investigation of these structures is a promising direction. For each construction it is analyzed and justified the influence of nonstationarity effects and persistence on the phase transfer also reviewed the related positive results. It is shown that research in this area will create intense mass transfer devices, which can be achieved by thermal mass transfer coefficients of growth exceeding the growth rate of the hydraulic resistance machines.